Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/jstp-01-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frontline employee's hope and consumer failure during consumer-created emergencies

Abstract: PurposeIn important interpersonal service interactions with a frontline employee (FLE), consumers at times fail to carry out their share of responsibility in the execution of the service, resulting in a situation of “consumer created emergency”. This might defeat the consumer's goal of availing the service (termed as consumer failure). This study explains the role of employee's hope in managing consumer failure in the situation of consumer created emergencies.Design/methodology/approachHypotheses were tested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 139 publications
(154 reference statements)
0
5
0
Order By: Relevance
“…However, in service settings, supervisors do not necessarily differentiate between in-role and extra-role behaviors when rating their subordinates' performance (Liao and Chuang, 2004; see also Kim and Carlson, 2016; Mehra et al , 2001; Lam et al , 1999). This is because service performance expectations surround the customer experience and typically involve an indefinite set of behaviors that help and serve customers (Liao and Chuang, 2004; Ranjan et al , 2021). We argue that this malleability in the customer-service role definition (Morrison, 1994) allows self-monitors to adapt and respond in a variety of ways that they determine to be appropriate to the situation they are attending and to fit in accordingly.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…However, in service settings, supervisors do not necessarily differentiate between in-role and extra-role behaviors when rating their subordinates' performance (Liao and Chuang, 2004; see also Kim and Carlson, 2016; Mehra et al , 2001; Lam et al , 1999). This is because service performance expectations surround the customer experience and typically involve an indefinite set of behaviors that help and serve customers (Liao and Chuang, 2004; Ranjan et al , 2021). We argue that this malleability in the customer-service role definition (Morrison, 1994) allows self-monitors to adapt and respond in a variety of ways that they determine to be appropriate to the situation they are attending and to fit in accordingly.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…Theoretical background and hypotheses development 2.1 Continuance intention to use M-payment M-payment conducts transactions via wireless technologies including radio frequency identification (RFID), mobile phone networks, Bluetooth and NFI (Franque et al, 2021). Various M-payment options have become popular, like online shopping apps and mobile wallets (Ranjan et al, 2021). In the Jordanian context, on 1/4/2014, the Jordan Mobile Payment (JoMoPay) app was officially launched, dramatically altering the payment services landscape (CBJ, 2022).…”
Section: Mobile Payment Service Quality 2019mentioning
confidence: 99%
“…M-payment conducts transactions via wireless technologies including radio frequency identification (RFID), mobile phone networks, Bluetooth and NFI (Franque et al ., 2021). Various M-payment options have become popular, like online shopping apps and mobile wallets (Ranjan et al. , 2021).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In addition, recent research has revealed that differences in emotional ability among customers affect attitude formation (Hasford et al, 2018). Perceiving the absence of negative emotion is vital for customers to identify and utilize service encounters, that is, the behavior of frontline service providers on managing negative traits and outcomes (e.g., in a healthcare context, hospital's supportive cocreation practices) (Mattila & Enz, 2002; Ranjan et al, 2021). Accordingly, in the healthcare service context, this study posits that customers who experience the absence of negative emotion are more likely to cope with stress, seek engagement opportunities, and potentially be enabled by PVCC, while customers compounded with negative emotions are less likely to exploit the cocreation opportunities offered by PVCC.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%